Eggs [compact disc, unabridged] - Spinelli, Jerry (Hachette Audio, 2007)
Mourning the loss of his mother, nine-year-old David forms an unlikely friendship with independent, quirky thirteen-year-old Primrose, as the two help each other deal with what is missing in their lives.